2009
DOI: 10.1007/s10546-009-9439-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Observational Analysis of the Bora of Pag’s Ribs

Abstract: The severe bora case that lasted from 13 to 15 November 2004 has been selected for the analysis of the bora of Pag's ribs, which occurs in the northern part of the eastern Adriatic coast over the Pag island area (Croatia). According to the measurements from automatic stations, the MM5 numerical model is successful in the 10-min mean wind speed prediction at 10-m height. The vertical analysis of the wind speed and potential temperature also gave satisfactory results. At the commencement of the bora the modelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…They found that atmospheric resolution, via a better reproduction of the orography and consequently the enhancement of jet flows on finer grids, is one of the most important model characteristics known to impact wind speed (Belušić et al, 2017). More specifically, for the bora events which are historically studied with (sub) kilometer-scale models (e.g., Grisogono & Belušić, 2009;Kuzmić et al, 2015;Prtenjak et al, 2010;Trošić & Trošić, 2010), a brief investigation by Josipović et al (2018) reveals that regional climate models (with a resolution of 0.11°) are incapable to represent wave-breaking. They thus should not be used to derive the changes in bora wind intensity under climate scenarios.…”
mentioning
confidence: 99%
“…They found that atmospheric resolution, via a better reproduction of the orography and consequently the enhancement of jet flows on finer grids, is one of the most important model characteristics known to impact wind speed (Belušić et al, 2017). More specifically, for the bora events which are historically studied with (sub) kilometer-scale models (e.g., Grisogono & Belušić, 2009;Kuzmić et al, 2015;Prtenjak et al, 2010;Trošić & Trošić, 2010), a brief investigation by Josipović et al (2018) reveals that regional climate models (with a resolution of 0.11°) are incapable to represent wave-breaking. They thus should not be used to derive the changes in bora wind intensity under climate scenarios.…”
mentioning
confidence: 99%